The Influence of Work Discipline and Intrinsic Motivation on Employee Performance at PT Kharisma Berkah Nusantara, Bekasi - Bambang Sutarto; Laila Irawati; Udin Saprudin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the influence of Work Discipline and Intrinsic Motivation on Employee Performance at PT Kharisma Berkah Nusantara, Bekasi. The research applies a quantitative approach with a descriptive-associative design. The population consists of 60 employees, and all employees were used as respondents through saturated sampling. Data were collected using Likert-scale questionnaires and analyzed with SPSS through validity, reliability, classical assumption, and multiple linear regression tests. The findings show that Work Discipline has a positive and significant effect on Employee Performance. Intrinsic Motivation also has a positive and significant effect, with a stronger influence than Work Discipline. Simultaneously, both variables affect Employee Performance in a significant way. The coefficient of determination shows that Work Discipline and Intrinsic Motivation explain 22.2% of Employee Performance, while 77.8% comes from other factors outside this study. This result indicates that employee performance cannot rely only on discipline and internal drive. PT Kharisma Berkah Nusantara needs to strengthen work discipline while also creating conditions that support personal responsibility, achievement, and employee commitment.